STIMULASI DALAM MEMAKSIMALKAN KEMAMPUAN BERBAHASA ANAK USIA DINI - Mulyaningtyas, Rahmawati (Martabat: Jurnal Perempuan dan Anak, 2019)
The language activities of early childhood are interesting things to study. A child develops language competencies from the use of the language of the people in the surrounding environment. The environment is one of the factors that determine children in acquiring language. Outer stimulation of the child can influence children in developing language skills. The discussion of this article is going to focus on stimuli that can be given to early childhood in supporting language activities.